Genetic profiles and prediction of the success of young athletes` transition from middle- to long-distance runs: An exploratory study - Ben-Zaken, S.; Meckel, Y.; Lidor, R.; Nemet, D.; Eliakim, A. (Pediatric Exercise Science, 2013)
The aim of the study was to assess whether an aerobic-favoring genetic profile can predict the success of a shift from middle- to long-distance running. Thirteen elite middle-distance runners were divided into successful and nonsuccessful groups in their shift toward long-distance runs. All the runners began their training program at the age of 14-15, and after 6-7 years, changed focus and adjusted their train- ing program to fit longer running distances. The participants` personal records in the longer events were set at the age of 25-27, about 3-5 years after the training readjustment took place. The endurance genetic score based on 9 polymorphisms was computed as the endurance genetic distance score (EGDS9). The power genetic distance score (PGDS5) was computed based on 5 power-related genetic polymorphisms. The mean EGDS9 was significantly higher among the successful group than the nonsuccessful group (37.1 and 23.3, respectively, p < .005, effect size 0.75), while the mean PGDS5 was not statistically different between the 2 groups (p = .13). Our findings suggest the possible use of genetic profiles as an added tool for determining appropriate competitive transition and specialization in young athletes involved in early phases of talent development.